Exploring the Role of Emotional Intelligence in Business Leadership (Research Studies of Business, 2024)
Emotional intelligence (EI) has emerged as a crucial component in effective business leadership. This paper investigates how emotional intelligence influences leadership effectiveness, employee engagement, and organizational performance. By examining the key elements of EI, including self-awareness, self-regulation, motivation, empathy, and social skills, the study highlights their impact on leadership practices and decision making processes. Through a review of current literature, case studies, and empirical research, the paper provides insights into the ways leaders can harness emotional intelligence to foster positive organizational outcomes and enhance their leadership capabilities. The findings underscore the importance of EI in building resilient and adaptive leaders who can navigate complex business environments.